Subjective and objective as a manifestation of opposition: a new perspective on classical approaches - Mkrtchyan, Mkrtich S. (Bulletin of Yerevan University B: Philology, 2023)
The subjective and objective differentiation of human perception of the world has always interested philosophers, semioticians, and to some extent linguists. Moreover, subjective meaning is interpreted differently by different linguists, and as a consequence, the views of subjective meaning as a linguistic phenomenon take on a different character among different linguists. There are also different views on who first formulated the idea of subjective meaning from a linguistic point of view. At the same time, the subjective and objective nature of the meaning is sometimes explicitly and sometimes implicitly present in the works that more or less refer to the use of the word. Perhaps Eduard Aghayan is one of the few Armenian linguists who has made a separate reference to the subjective meaning of the word, underlying the cases when the word meaning denoting an objective concept acquires a subjective meaning and subjective semantic coloring. Accordingly, this article aims to first examine the understanding of subjective meaning in linguistics, the relationship between subjective and objective from the perspective of cognitive linguistics, and then present Eduard Aghayan’s views on the manifestation of the subjective meaning of a word in his various works.